Sliding mode wheel slip controller for an antilock braking system. (5th August 2014) - Will, A.B.; Hui, S.; Zak, S.H.
A nonlinear control system that combines a sliding mode based optimiser and a proportional–plus–integral–plus–derivative (PID) controller is presented for a vehicle antilock brake system. The sliding mode optimiser performs an on–line search for the optimal wheel slip that corresponds to the vehicle's maximum deceleration. The PID controller and the sliding mode optimiser are coupled to regulate the vehicle's brake torque to control the wheel slip to its optimal value. The performance of the proposed control schemes is illustrated with simulation examples.